Dynamic mathematical design and modelling of autonomous control of All-Terrain Vehicles (ATV) using system identification technique based on pitch and yaw stability - Mohd Aras, Mohd Shahrieel; Mohd Zambri, Mohd Khairi; Ab Rashid, Mohd Zamzuri; Abdul Azis, Fadilah; Khamis, Alias (Praise Worthy Prize, 2015)
This research describes the dynamically mathematical design and modelling of autonomous control of all-terrain vehicles (ATV) using system identification technique based on pitch and yaw stability. The modelling of ATV using dynamic mathematical method based on single track model which the left and right tires for both front and rear have the same characteristics. The main difficulty of the ATV control is the steering control which could not rotate easily and need higher forces to control the ATV movement manually. The movement is very limited when driving the ATV manually, since it requires a strong thrust to move the steering. Therefore, the design of wireless control system is use to solve the problem which could control the rotation angle of 45° to the left and right with precision, and accuracy on the steering control. First, the modelling of ATV will be derived using Newtonian formulation, and also design the controller of the ATV with accordance to the path-following planning motion method. The results for stability of ATV is validate using a model generated by MATLAB system identification toolbox. The best fit for yaw estimation is 92.7% and whereas pitch estimation is 69.76% respectively. As a conclusion, the yaw estimation shows that the ATV achieved its stability at the angle 45° and verify simulated of yaw axis part.